Tripartite Free Trade Agreement as a solution to increasing intra-African trade - Dari, Teurai Thirdgirl (University of the Western Cape, 2016)
Magister Legum - LLM === Trade has been widely accepted as an important tool in spearheading economic growth and development. In many different parts of the world, countries have alleviated poverty and economically prospered through effective trade. Despite the efforts to dismantle trade restrictions and create a common market, the problem remains that of African disintegrated markets which then lead to poor intra-African trade. There is therefore the need to use intra-African trade as an instrument that effectively serve in the attainment of rapid and sustainable social and economic development. The aim of this study is to therefore determine whether the solution to increasing intra-African trade can be found in the Tripartite FTA.